Idiopathic multifocal retinal pigment epithelium detachment – case report - Wróbel-Dudzińska, Dominika; Dolar-Szczasny, Joanna; Żarnowski, Tomasz; Święch-Zubilewicz, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
The aim is to report the case of a 26-year-old woman with idiopathic multifocal detachment of the retinal pigment epithelium, posing a diagnostic challenge relative to differential diagnosis. A complete ophthalmic assessment including fluorescein angiography and optical coherence tomography was performed. Conclusions: As supported by published data, idiopathic multifocal retinal pigment epithelium detachment may resolve spontaneously without treatment, not leading to permanent vision impairment.